1999
DOI: 10.1128/jcm.37.12.3896-3900.1999
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of OropharyngealCandidaColonization and Infection in Patients Receiving Radiation for Head and Neck Cancer

Abstract: Oral mucosal colonization and infection with Candidaare common in patients receiving radiation therapy for head and neck cancer. Infection is marked by oral pain and/or burning and can lead to significant patient morbidity. The purpose of this study was to identify Candida strain diversity in this population by using a chromogenic medium, subculturing, molecular typing, and antifungal susceptibility testing of clinical isolates. These results were then correlated with clinical outcome in patients treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
3
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 22 publications
4
90
3
3
Order By: Relevance
“…An increased incidence of candidiasis before and during radiation therapy, as well as several years after completed radiation therapy has, been reported (Redding et al, 1999;Schwarz et al, 1999). In this study, 6-8 months after completed radiation therapy, we found no clinical signs of mucosal infections in the RT group.…”
Section: Mucosal Samplessupporting
confidence: 48%
“…An increased incidence of candidiasis before and during radiation therapy, as well as several years after completed radiation therapy has, been reported (Redding et al, 1999;Schwarz et al, 1999). In this study, 6-8 months after completed radiation therapy, we found no clinical signs of mucosal infections in the RT group.…”
Section: Mucosal Samplessupporting
confidence: 48%
“…fludarabine), in graft-versus-host disease (GvHD) or after radiation therapy. [4][5][6] Other predisposing factors include diabetes mellitus, therapy with antibacterial agents or local factors such as the use of a dental prosthesis. [7][8][9] Most infections are caused by yeast that colonise the skin or mucous membranes.…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%
“…4 Status of licensing. 5 Not sufficiently validated in children below 13 years. 6 Potential for interactions, benefits compared with fluconazole undefined.…”
Section: Central Nervous System Candidosismentioning
confidence: 99%
“…The conditions that place patients at risk for OPC are different from the risk factors for haematogenously disseminated candidiasis (HDC) (Wright and Wenzel, 1997), suggesting that the pathogenesis of OPC is different from HDC. Approximately 85% of episodes of OPC are caused by Candida albicans, either alone or in combination with other species of Candida (Sangeorzan et al ., 1994;Redding et al ., 1999) . The mechanisms by which C. albicans causes oropharyngeal disease are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%